ANALISIS PERUBAHAN FUNGSI LAHAN SAWAH DI KOTA GORONTALO - Muhammad Rijal Syukri; Sri Sutarni Arifin (Universitas Negeri Gorontalo, 2021)
The use of paddy fields is an activity where a land is functioned as wet agricultural land or more commonly known as rice fields. The change in land use which was previously used as rice fields to other uses, especially in urban areas, has experienced a fairly high increase. This study aims to analyze the changes in the function of paddy fields in Gorontalo City in the last 10 years. The method used in this research is spatial analysis using a Geographic Information System (GIS) using historical imagery data from Google Earth. The results showed that there was a change in the function of paddy fields in Gorontalo City in a period of 10 years from 2010 to 2020. Changes in the function of paddy fields are in the form of built-up areas and dominated by settlements.. Keywords: changed, land, paddy field, function